Lexical typology and polysemy patterns in African languages - (:unkn) unknown (My University, 2017)
The RefLex reference comparative database for African languages (Segerer & Flavier 2011-2016) covers over a million entries for over 700 languages. Included are sets of search tools for polysemy patterns that ease identification of areal or genetical patterns of colexification for intrafield and transfield polysemies, as well as a map tool to visualize them. Partly building on previous works, this presentation will first present some results in several semantic domains: sensory modalities, (some) body parts, temperature (hot/warm; cold), child, want, and work. It will then discuss methodological, theoretical and heuristic issues related to the following questions: How does type of data frame our view of polysemy (dictionaries, grammars, intuition, questionnaires, large databases)? How to identify what is not universal, not borrowed, not inherited? These questions represent real challenges from Sprachbund studies, diachronic and typological studies alike.
Keywords: African Research